1990
DOI: 10.1017/s0020268100043031
|View full text |Cite
|
Sign up to set email alerts
|

Projecting the spread of AIDS in the United Kingdom: a sensitivity analysis

Abstract: In AIDS Bulletins Nos. 1 to 4 the Institute of Actuaries AIDS Working Party presented projections of HIV infection and AIDS based on a model developed by Wilkie. This paper explores the sensitivity of those projections to the various different assumptions which have to be made and presents results on a number of alternative sets of assumptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The exact choice of incubation period distribution was found to affect the peak of both HIV [40] and AIDS incidence [40,114] but the endemic prevalence was less affected. Conversely, one study showed that the long-term HIV incidence can be markedly decreased by only a slight increase in the mortality rate amongst HIV-infected MSM due to a smaller number of people that can pass infection to others [34].…”
Section: Effects Of Parameter Uncertainty On Hiv Epidemic Forecastsmentioning
confidence: 98%
See 3 more Smart Citations
“…The exact choice of incubation period distribution was found to affect the peak of both HIV [40] and AIDS incidence [40,114] but the endemic prevalence was less affected. Conversely, one study showed that the long-term HIV incidence can be markedly decreased by only a slight increase in the mortality rate amongst HIV-infected MSM due to a smaller number of people that can pass infection to others [34].…”
Section: Effects Of Parameter Uncertainty On Hiv Epidemic Forecastsmentioning
confidence: 98%
“…1986 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 forecasts of the HIV MSM epidemic [37][38][39][40] and all dated back to before 1991.…”
Section: Epidemic Projectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model put forward by the Institute of Actuaries AIDS Working Party (Daykin et al, 1988(Daykin et al, , 1990) is used as a representation of the transmission and spread of AIDS among male homosexuals.…”
Section: Introductionmentioning
confidence: 99%